Good idea, bad prerequisite, zero result – the meaning of context in implementing aftercare for young people in secure unit care. Issue 3 (9th September 2014) - Andersson Vogel, Maria; Sallnäs, Marie; Lundström, Tommy
Abstract : Purpose: – The purpose of this paper is twofold: first, to report results from a quasi-experimental study of outcomes of a leaving care project for youth placed in secure unit care and second, based on the (zero) results, to analyse and discuss the interplay between organisational boundaries, social work and the target group when implementing a project such as the one studied. Design/methodology/approach: – The outcome study had a quasi-experimental design. The young people in the leaving care programme were compared with a matched reference group who did not get the special leaving care services. Data were collected (structured Adolescent Drug Abuse Diagnosis-interviews) when the young people entered secure units and on follow-up (registered crime and re-entry into care). Findings: – The outcome study showed that the leaving care project had no effect on the young people's situation at follow-up regarding re-offending and re-entry into secure unit care. This is understood and discussed in relation to the poor implementation of the leaving care project along with an inbuilt conflict between state and local municipality that overshadowed the good intentions of the project. Research limitations/implications: – The effect study has a quasi-experimental design, and hence differences between the project group and the comparison group at T1 cannot be fully precluded, although nothing is pointing in such a direction. The unclear content of the intervention makes it difficult to decode how the variation in the support given to the young people eventually impacted the results. The zero-results apply to group level, but that may not be valid for each and every one in the project. Practical implications: – According to earlier research, a key person following young persons through different phases of the care trajectory may be of importance. Learning from the CoC project, one can conclude that such a key person should preferably take the role of advocate for the young person, and not be an administrator mainly concerned with coordinating other professionals. Further, when planning and financing is split between organisations, that split hinders efforts to actually mobilise support for young people leaving secure unit care. Originality/value: – Few leaving care services are designed for youth with severe behavioural problems and hence, the research is scarce. This study contributes with important knowledge about leaving care interventions for the target group.